Pemanfaatan Media Pembelajaran Audio Visual Berbasis Channel Youtube dalam Pembentukan Karakter Anak di Taman Pendidikan Al-Qur’an - Devina Ramadhani; Dedi Setiawan; Rina Mida Hayati (Bustanul Ulum Journal of Islamic Education, 2024)
Character education should be implemented from an early age because early age really determines a child's ability to develop their potential. Problems found at Al-Ikhsan TPA include not respecting ustadz, rarely reciting the Koran, behaving impolitely, and there are still people who say dirty words at Al-Ikhsan TPA, Terbanggi Besar District. This research is field research with a qualitative descriptive nature, while the data analysis method uses a deductive method. Utilization of Audio Visual Learning Media Based on YouTube Channels in Forming Children's Character at Al-Ikhsan TPA, namely First, Introduction by preparing equipment including TV, Wifi and YouTube channels. Second, Exploration, namely students have diverse characters, activated through active, innovative, creative, effective and fun learning methods. Third, restructuring, namely the concept of learning by watching YouTube channels and continuing with the question and answer method. Fourth, implementation, namely a 60 minute learning process by broadcasting a YouTube channel about the stories of prophets and apostles. Fifth, Review or Evaluation, namely a question and answer session to evaluate children's understanding of the meaning contained in the YouTube channel. The use of audio visual media based on YouTube channels can shape the character of children at Al-Ikhsan TPA, especially children who have religious, honest, curious, hard working, social care and responsibility characters. Learning using the YouTube channel has several obstacles, including an unstable network and bad weather, resulting in changes to the learning schedule. Therefore, researchers provide recommendations in the form of adding a learning schedule by utilizing the YouTube channel 2-3 times a week, this is done so that children's character formation becomes more effective and optimal.